Microwave-assisted reduced graphene oxide from vacuum gas oil derived graphitic carbon: An innovative solution for wastewater treatment and oil spill control - Ravi Dalsania; Hasmukh Gajera; Mahesh Savant (Desalination and Water Treatment, 2025)
Graphitic carbon derived from vacuum gas oil (VGO) was chemically oxidized to produce graphene oxide (GO), which was then reduced through sudden thermal treatment and microwave-assisted reduction to obtain reduced graphene oxide (rGO) and rGO-M, respectively. Leveraging VGO’s rich carbon content, this eco-friendly synthesis produced graphene-based materials with enhanced adoption capacity, thermal stability, and structural integrity. The rGO-M synthesis was optimized using Box-Behnken Design (BBD), adjusting microwave power (200 W), reduction time (30 s), and H₂O₂ concentration (5 mL), achieving up to 95 % removal efficiency. Structural, surface, and adsorption characteristics were evaluated for both rGO and rGO-M, particularly in wastewater treatment and oil spill cleanup. rGO-M showed superior adsorption capacity, removing 80 % of total hardness (initial: 170 mg/L) and 60 % of total organic carbon (TOC; initial: 22.74 mg/L) at 1.0 g/L dosage. At 1.5 g/L, it achieved 85 % and 61 % reductions in total hardness and TOC, respectively. For oil removal, rGO-M adsorbed 190 mg/g in 30 min, improving from 40 % efficiency at one minute to 95 % at thirty. While rGO had slightly higher efficiency, rGO-M stands out for its energy-efficient, simple preparation process and excellent performance.